Comparison of activity coefficient models for the estimation of uranyl nitrate and nitric acid distribution coefficients in phosphoric solvent. (October 2020) - Balasubramonian, S.; Pandey, N.K.; Subba Rao, R.V.
Abstract: The modelling of solvent extraction system is important for the process flow sheet design and optimization. The estimation of aqueous phase activity coefficients constitutes the major part of the thermodynamic modelling of solvent extraction system. Hence the selection of suitable activity coefficient models for the accurate description of aqueous electrolyte system encountered in the nuclear fuel reprocessing system is an important task which decides the accuracy and complexity of the modelling. In this work the accuracy of extended UNIQUAC (eUNIQUAC) activity coefficient model for the estimation of uranyl nitrate and nitric acid distribution coefficient in 1.1 M Tri Butyl Phosphate (TBP) and 1.1 M Tri iso Amyl Phosphate (TiAP) have been compared with the eNRTL, Pitzer and SIT activity coefficient models. eUNIQUAC model gave lowest RMSD (%) for the estimation of uranyl nitrate and nitric acid extraction in TiAP and TBP respectively. Graphical abstract: Image 1 Highlights: The extraction of uranyl nitrate and nitric acid to the organic phase containing 1.1 M TBP and 1.1 M TiAP was modeled. The estimation of organic phase solute concentration by eUNIQUAC model was compared with the eNRTL, Pitzer and SIT models. eUNIQUAC model gave lowest RMSD for the estimation of UO2 (NO3 )2 and HNO3 extraction in TiAP and TBP respectively. Pitzer model gave lowest RMSD during the estimation of water activity in the binary and ternary mixtures .